Investigation of Stability and Control Shortcomings of the North American X-15 - William P. Lorenzo; Ramana V. Grandhi; Timothy T. Takahashi (Aerospace)
There is growing interest in the design of maneuvering high-speed aircraft to fly within or at the edge of the atmosphere. We identify and develop novel quasi-static vehicle screening methodologies, suitable for use during preliminary design, to better predict an incipient loss of control due to the dynamic effects of feedback. We validate these metrics by reverse-engineering Neil Armstrong’s 1962 loss of control and inadvertent atmospheric skip while piloting the X-15. In 1962, then-extant flight dynamics screening methods did not forecast likely troubles. We assemble and refine a collection of predictive metrics which operate upon basic quasi-static aerodynamic data and predict the confluence of lateral/directional stability and controllability issues which plagued the flown mission. These tools, which leverage McRuer’s “equivalent stability derivative” approach, enable future engineers to make proactive design changes which can avoid lateral/directional instabilities developing at high speeds.